Modeling Fresh Product Delivery Routes with Heterogeneous Vehicle Routing Problem with Time Windows and Multi-Trips Model: A Case Study - Asbowo, Heri; Sirajuddin, Sirajuddin; Ilhami, Muhammad Adha (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study develops a Heterogeneous Vehicle Routing Problem with Time Windows and Multi-Trips (HVRPTWMT) model designed to minimize delivery distances for fresh products. The model addresses complex operational constraints inherent in real-world logistics, including time windows, heterogeneous fleets, and multi-trip requirements. A quantitative approach was employed to formulate the HVRPTWMT model, which was then solved using an analytical method to ensure a global optimum solution was found. The model's efficacy was demonstrated through its application to historical data from April 10, 2025, yielding an optimal total distance of 774.45 km across six efficient routes. Sensitivity analysis confirmed the model's robustness and responsiveness to critical parameter changes, such as vehicle capacity, demand fluctuations, and time limits. The developed HVRPTWMT model provides a globally optimal and rule-compliant solution for complex fresh product delivery logistics.